Phase I trial evaluating the safety and immunogenicity of candidate TB vaccine MVA85A, delivered by aerosol to healthy M.tb-infected adults - Riste, M; Marshall, JL; Satti, I; Harris, SA; Wilkie, M; Lopez Ramon, R; Wright, D; Wittenberg, RE; Vermaak, S; Powell Doherty, R; Lawrie, A; Conlon, CP; et al. (MDPI, 2021)
The immunogenicity of the candidate tuberculosis (TB) vaccine MVA85A may be enhanced by aerosol delivery. Intradermal administration was shown to be safe in adults with latent TB infection (LTBI), but data are lacking for aerosol-delivered candidate TB vaccines in this population. We carried out a Phase I trial to evaluate the safety and immunogenicity of MVA85A delivered by aerosol in UK adults with LTBI (NCT02532036). Two volunteers were recruited, and the vaccine was well-tolerated with no safety concerns. Aerosolised vaccination with MVA85A induced mycobacterium- and vector-specific IFN-γ in blood and mycobacterium-specific Th1 cytokines in bronchoalveolar lavage. We identified several important barriers that could hamper recruitment into clinical trials in this patient population. The trial did not show any safety concerns in the aerosol delivery of a candidate viral-vectored TB vaccine to two UK adults with Mycobacterium tuberculosis (M.tb) infection. It also systemically and mucosally demonstrated inducible immune responses following aerosol vaccination. A further trial in a country with higher incidence of LTBI would confirm these findings.